2022
DOI: 10.1007/s11356-022-24045-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of nutrigenomics and dietary components as a complementary therapy in cancer prevention

Abstract: Cancer is an illness characterized by abnormal cell development and the capability to in ltrate or spread to rest of the body. When this abnormal development progresses in solid tissues, such as an organ, muscle, or bone it is known as tumour, which can spread to other regions of the body via the blood and lymphatic systems. Nutrition is a critical and immortal environmental component in the development of all living organisms encoding the relationship between a person's nutrition and their genes. These intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 235 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…Water microorganisms will form proteins when the nutrients in the cultivation medium are sufficient, and measurements are usually taken when entering the exponential phase. Srivastava et al (2022), if there is a lack of macronutrients, microalgae cells will experience a decrease in protein content followed by degradation of other cell components related to protein synthesis. Pinandoyo et al (2021) also stated that the nutritional content that can be utilized optimally would increase growth.…”
Section: Total Protein Contentmentioning
confidence: 99%
“…Water microorganisms will form proteins when the nutrients in the cultivation medium are sufficient, and measurements are usually taken when entering the exponential phase. Srivastava et al (2022), if there is a lack of macronutrients, microalgae cells will experience a decrease in protein content followed by degradation of other cell components related to protein synthesis. Pinandoyo et al (2021) also stated that the nutritional content that can be utilized optimally would increase growth.…”
Section: Total Protein Contentmentioning
confidence: 99%
“…1,2 Investigations suggested that dietary phytochemicals can help to prevent cancer and even have been found to improve oncopatients' quality of life. [3][4][5] The molecular basis of these bioactive compounds' actions may provide new opportunities for the scientific community to create or enhance innovative treatment strategies to treat horrible illnesses, such as cancer, cardiovascular disease, and neurodegenerative disorders. A bioactive polyhydroxy flavone called wogonin (5,7-dihydroxy-8-methoxyflavone) was discovered in Scutellaria baicalensis Georgi.…”
Section: Introductionmentioning
confidence: 99%